Cost analysis of informal care: estimates from a national cross-sectional survey in Sweden - Björn Ekman; Kevin McKee; Joana Vicente; Lennart Magnusson; Elizabeth Hanson (BMC, 2021)
Abstract Background Over the past decades, informal care has increased in most OECD-countries. Informal care is costly to caregivers and to society in the form of lost income and direct costs of providing care. Existing evidence suggests that providing informal care affects caregivers' overall health. However, estimates of the social costs of informal care based on national data on individuals are currently scarce. Objective This study contributes to the existing evidence on the costs of informal care by estimating the direct and indirect costs to caregivers using a purposive national household survey from Sweden. Methods Adopting a bottom-up, prevalence approach, the direct and indirect costs are estimated using the survey data and the value of working time and leisure time from existing sources. Results The results suggest that around 15% of the adult population of Sweden provide informal care and that such care costs around SEK 152 billion per year (around 3% of GDP; USD 16,3 billion; EUR 14,5 billion), or SEK 128000 per caregiver. Around 55% of costs are in the form of income loss to caregivers. The largest cost items are reduced work hours and direct costs of providing informal care. Replacing informal caregivers with professional care providers would be costly at around SEK 193,6 billion per year. Conclusions Findings indicate that, even in a country with a relatively generous welfare system, significant resources are allocated toward providing informal care. The costing analysis suggests that effective support initiatives to ease the burden of informal caregivers may be cost-effective.